Study on the Concentrations and Correlation Coefficient of Cadmium and Zinc in Human Teeth ICP-AES - Maah, M.J.; Lee, C.B.; Amin, Y.M. (Nihon Bunseki Kagakkai (Japan Society for Analytical Chemistry), 2001)
Cadmium and zinc are the traceable elements in human teeth. These elements were analyzed by the technique of ICP-AES. The measurement results referred to the 199 samples of male and female donors, which were collected from the areas of Klang Valley and Malacca. ...